Furrow-and-ridge morphology on rockglaciers explained by gravity-driven buckle folding: A case study from the Murtèl rockglacier (Switzerland) - Frehner, Marcel; Ling, Anna H. M.; Gärtner-Roer, Isabelle (Permafrost and Periglacial Processes, 2015)
ISSN:1045-6740 ISSN:1099-1530